What has rural life to offer? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Recent decades have witnessed a growing tide of migration of rural people to large urban centres. The flight from country to town has been both because of the lure of city life - employment, social amenities, and escape from traditional social...